Face-to-face versus Video Teleconference Group Cognitive Behavioural Therapy for Anxiety and Related Disorders: A Preliminary Comparison. (May 2022) - Milosevic, Irena; Cameron, Duncan H.; Milanovic, Melissa; McCabe, Randi E.; Rowa, Karen
Objective: Telehealth is being increasingly incorporated into the delivery of mental health care and has received widespread attention during the COVID-19 pandemic for its ability to facilitate care during physical distancing restrictions. Videoconferencing is a common telehealth modality for delivering psychotherapy and has demonstrated similar outcomes to those of face-to-face therapy. Cognitive behavioural therapy (CBT) is the most common psychotherapy evaluated across various telehealth modalities; however, studies on CBT delivered via videoconference, particularly in a group therapy format, are lacking. Further, little research exists on videoconference group CBT for anxiety disorders. Accordingly, the present study compared the outcomes of group CBT for anxiety and related disorders delivered via videoconference versus face-to-face. Method: Using a non-randomized design, data on attendance, dropout, clinical outcomes, and functional impairment were collected from 413 adult outpatients of a tertiary care anxiety disorders clinic who attended a CBT group for panic disorder/agoraphobia, social anxiety disorder, generalized anxiety disorder (GAD), or obsessive-compulsive disorder delivered either face-to-face (pre-COVID-19 pandemic) or via videoconference (since the onset of COVID-19 pandemic). Outcomes were assessed using well-validated self-report measures. Data were collected pre-treatment, across 12 weekly sessions, and post-treatment. Intent-to-treat analyses were applied to symptom outcome measures. Results: Face-to-face CBT conferred only a slight benefit over videoconference CBT for symptom outcomes across all groups, but when assessed individually, only the GAD group showed greater symptom improvement in the face-to-face format. Effect sizes for significant differences between the delivery formats were small. Participants in videoconference groups tended to have slightly higher attendance rates in some instances, whereas functional improvement and treatment dropout were comparable across the delivery formats. Conclusions: Results provide preliminary evidence that videoconference group CBT for anxiety and related disorders may be a promising and effective alternative to face-to-face CBT. Additional research is needed to establish equivalence between these delivery formats.